Risk factors associated with gradual onset running-related injuries in 5770 ultramarathon race entrants - SAFER XXXII - Slabber, K.; Schwellnus, M. P.; Ramagole, D.; Boulter, J.; Dyer, M.; Jordaan, E.; Sewry, N. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: There is limited evidence available on contributing factors for gradual onset running-related injuries (GORRIs) in ultramarathon runners. The aim was to determine if selected risk factors were associated with a history of GORRIs in 90-km ultramarathon race entrants. METHODS: Descriptive cross-sectional study. GORRI and medical data using an online pre-race medical screening tool was collected from 5770 consenting race entrants from the 2018 90-km Comrades Marathon. Selected risk factors associated with 12-months history of GORRIs (age, sex, training, chronic diseases and allergies) were analyzed using a multiple model (Poisson regression). Prevalence and prevalence ratios (PR, 95% CIs) are reported. RESULTS: The overall 12-month prevalence of GORRIs was 11.6% (95% CI: 10.8-12.5) and this was higher in females versus males (PR=1.6; 1.4-1.9) (P<0.0001). Novel independent risk factors associated with a history of GORRIs were: history of chronic disease (PR=1.3; P=0.0063); history of allergies (PR=1.7 increased risk for every disease; P<0.0001); fewer training sessions/week (PR=0.8 decreased risk for every two additional training sessions per week; P=0.0005); and increased number of years as a recreational runner (PR=1.1 increased risk per 5 years of running; P=0.0158). CONCLUSIONS: There is a complex interaction between the internal and external risk factors associated with GORRIs in 90-km distance runners. These data can inform injury prevention programs targeted at subgroups of ultradistance runners.